Pneumocystis exhalation by infants developing Pneumocystis primary infection: putative infectious sources in hospitals and the community. (July 2021) - Pougnet, L.; Hoffmann, C.V.; Pougnet, R.; Le Ny, F.; Gaitan, L.; Cros, P.; Artus, M.; Le Gal, S.; Nevez, G.
Summary: Pneumocystis jirovecii DNA was detected using a polymerase chain reaction assay in air samples collected using an air–liquid impaction device at 1 m distance from three out of 14 infants who had developed Pneumocystis primary infection. P. jirovecii genotype identification was successful in one out of three pairs of air samples. Matching of P. jirovecii genotypes between the nasopharyngeal and air samples suggested that P. jirovecii was effectively exhaled by the infected infant. These original results represent a proof of concept of the role of infants with primary pneumocystis infection as infectious sources of P. jirovecii in hospitals and in the community.